Pemenuhan Kebutuhan Istirahat dan Tidur pada Lansia dengan Terapi Dzikir Di PSTW Tresna Werda Budi Luhur Jambi - Faridah Faridah; Iin Indrawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Sleep is a form of activity that affects the quality of individual health. Insomnia is a symptom that can interfere with the activity and productivity of the elderly. Therefore the elderly must get appropriate therapy. Therapy in patients with insomnia can be in the form of pharmacological therapy or nonpharmacological therapy, but pharmacological therapy can cause an effect on the side compared to non pharmacological therapy.Tresna Werdha Budi Luhur Social Home is a nursing home in Jambi, which accommodates elderly people so that they get proper care. The number of elderly people who were there in 2010 as many as 73 homes, 37 men and 35 women. Based on a preliminary survey conducted in July 2019, the elderly generally complained of not being able to sleep soundly so that they felt weak, lethargic and not eager to do activities during the day. The sleep disturbance is felt when you wake up at night, for example listening to the full sound, the urge to urinate, and there are also those who find it difficult to fall asleep. The solution to these problems is counseling the elderly who have sleep disorders, training in the application of remembrance therapy to the elderly. The target outputs that have been implemented are the development of teaching materials in the nursing nursing course and counseling turning sheets. The method used is discussion, socialization and demonstration on counseling and practice directly with elderly dhikr therapy. The results that have been achieved are the elderly are very good and want to do this remembrance therapy if they have difficulty sleeping, but for this early stage the elderly need assistance to understand the steps of the practice of remembrance therapy